(untitled) (Scientific journal of the Fergana State University, 2023)
This article is dedicted to the role and importance of monumental painting in our country today, as well as the visual arts and creative skills of the great artist Alisher Alikulov.. The elegant drawings in the works of Alisher Alikulov reflect the artist`s view on the art world.